Types, Management and Complications of Trachiobronchial Foreign Bodies (Medical Forum Monthly, 2024)
Objective: To determine the types, management and complications of tracheobronchial foreign bodies.Study Design: cross sectional studyPlace and Duration of Study: This study was conducted at ENT Department of Nishtar Hospital Multan from January 2010 to December 2011.Patients and Methods: 150 patients underwent rigid bronchoscopy under general anesthesia after routine investigations and x-rays chest where feasible.Results: A total 150 patients underwent bronchoscopy for diagnostic as well as therapeutic purposes. Most common foreign bodies were peanuts (40.66%), beetle nuts (18.66%) and whistles (18.66%). In 137 (91.33%) patients, foreign bodies were removed on bronchoscopy at first attempt. 10 (6.67%) cases were diagnostic and only 2 (1.33%) cases were subjected to open surgical removal. One (0.67%) of the patients died in ICU after removal of foreign body.Conclusion: Early diagnosis and timely management of foreign bodies with bronchoscopy saves patients life and avoids complications. Younger children should not be offered peanuts, whistles or toys that can be inhaled.